The Age of Datum or Data as a Methodological Paradigm. - Federici, Valeria (Italianist, 2022)
This article illustrates how, like photography in the late nineteenth century, data often possesses an alluring appearance of objectivity which gives it affordance. It reflects on how data has altered methods of investigations and, while rejecting its use as a mere indexical trace of information that leads to unequivocal conclusions, advocates for the humanist's intervention in directing how data is collected, prepared, used, and displayed. The article explores and illustrates three platforms: MediaWiki and its applications, including the Semantic Web; IIIF (International Image Interoperability Framework), a tool designed to replicate traditional image-comparative methodologies within a digital realm; and FromThePage, a text transcript platform. Finally, the conundrum of web archiving and data preservation is analysed, to reflect on how data has marked a paradigm shift in our perception, expectations, and understanding of methodologies in the humanities.